2017
DOI: 10.1093/jisesa/iex097
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Alarm Pheromone of Cowpea Aphid, and Comparison With Two Other Aphididae Species

Abstract: In response to a predator attack, many Aphidinae species release an alarm pheromone, which induces dispersal behavior in other individuals within the colony. The major component of this pheromone is the sesquiterpene (E)-β-farnesene (Eβf), but variations occur between aphid species. In the present work, we collected, identified, and quantified the alarm pheromone of Aphis craccivora Koch (Hemiptera: Aphididae), before quantifying the escape behavior induced in the neighboring individuals. We compared the semio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In our alarm‐response assays we found a fraction of ~35% peach aphids responding to pyrethrum flower volatiles. This is in line with studies reporting 20–40% of peach aphids responding to 50–500 ng synthetic EβF (Bayendi Loudit et al ., ). It is common across species that only a fraction of the aphids respond to alarm pheromones, which probably balances the advantages of sustaining the colony with the risks of starting a new one (de Vos et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In our alarm‐response assays we found a fraction of ~35% peach aphids responding to pyrethrum flower volatiles. This is in line with studies reporting 20–40% of peach aphids responding to 50–500 ng synthetic EβF (Bayendi Loudit et al ., ). It is common across species that only a fraction of the aphids respond to alarm pheromones, which probably balances the advantages of sustaining the colony with the risks of starting a new one (de Vos et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…β-farnesene belongs to the sesquiterpene class. It is naturally produced by many plant species and by aphids as an alarm pheromone 74 . More recently, it is also studied as a potential anti-inflammatory modulator of human neutrophils 75 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, (E)-β-farnesene (EβF) is a VOC that serves as an alarm pheromone in numerous aphid species. It is released in response to a predator attack, inducing dispersal behaviour in conspecifics [85]. Lin and colleagues [12] demonstrated that EβF release induced the dispersal of M. persicae and M. euphorbiae influencing the spread of phytoviruses under laboratory conditions.…”
Section: Biochemical Componentsmentioning
confidence: 99%